Finite Element Method Analysis of Normal and Corrosion Buckling with ANSYS17 Program for Stainless Steel 304 Alloy - Jasim AL Akawai, Hussain; Mershid Aweed, Khalid; Ali Jaber, Shawthab (International Journal of Engineering and Technology, 2018)
In the present research the effect of corrosion on buckling behavior of 304 stainless steel with increasing of compressive dynamic loads was studied. There are two types of the columns, long columns and intermediate columns were used. For compression test, there are 24 columns specimens were used in the dynamic axis, 12 columns tests were carried out with increasing in the dynamic axis of compressive load, while for the corrosion test was performed by using 12 specimens were buried for two months under the ground before tested them. The allowable deflection in lateral axis is 1% in the length of column. When the deflection in lateral axis reaches 1% and does not increase more than it, and when removing the applied load, the column will return back to the normal state. This is defined critical buckling of columns. To calculate the original deflection. The digital gauge was employed at the distance about 0.7 for the column length at the fixed end of column. has alarm system was used to define critical buckling and to avoid the failure of the specimen and installed at the distance equal to 0.7 of the column length from fixed end. The empirical results showed that the effect of negatively corrosion on mechanical properties of alloys with 2.53% reduction of ultimate tensile strength comparing with non corroded specimens, in the other hand the corrosion will reduce the critical buckling load by 6% for two months. The experimental results comparing with the theoretical results obtained by Perry Robertson and Euler. Johnson with the results analyzed by ANASYS17. The results of this work are agreed with Perry-Robertson and Euler- Johnson by a safety factor about (1, 3) and 3 respectively while the results of ANASYS showed that agreement with the calculated and measured values by safety factor about (2).Â Â